A revised proposed methodology to investigate shari'ah compliance in the formation of construction contract - Abdullah Habib, Siti Nora Haryati; Abdul Rashid, Khairuddin (2008)
A study is being currently undertaken to examine the current practice of construction procurement with specific reference to contract formation and appraises the practice in terms of its compliance with the Shari'ah. The focus of this paper is on the methodology being proposed i.e. to study the practice of the offer and acceptance during contracting out construction works whereby the research model is presented herein.1 The study is expected to determine whether the current practice of the offer and acceptance in the formation of construction contract in compliance or otherwise with the Shari'ah. The proposed methodology combines two key data sources" i.e. (i) literature review; and (ii) series of focus group discussions with people who are considered as experts in the fields of construction procurement and fiqh al-muamalat. Comments and recommendations are neede in order to improve the methodology.